Repercussion of diabetes mellitus in the sexuality of male patients regular attendants to 'Violeta Parra' Doctor's office in Chiclan, Chile, 2003 - Ximena Isla Lund; María José Aguilera Meriño; Paula Arancibia Castro; Carolina Barriga Jungjohann; Nelly Gálvez Chávez (Universidad de Alicante, 2012)
Descriptive, retrospective and cross-sectional study, whose aim was discovering to what extent could Diabetes Mellitus affect the sexuality of males. They were regular patients/clients of the Urban General 'Violeta Parra' Doctor's Office in Chillan, Chile. The instrument used was a survey, adapted by the authors themselves, including a scale to measure the repercussion of Diabetes Mellitus in the sexuality of males, and a sub-scale of 'couple relationship', both questionnaires validated by doctors Eduardo Pino and Elena Sepúlveda. In addition, the Morris Rosemberg's Self-esteem Scale, modified by the researchers themselves, was also used. A sample of 100 males selected at simple random was taken, bearing in mind a criterium for exclusion of a universe of 391 male clients/patients from the Urban General 'Violeta Parra' Doctor's Office of Chillan. The study was based on theoretical and empirical backgrounds demonstrating Diabetes Mellitus produces Sexual Erectile Dysfunction (SED) as a direct consequence of vascular changes and most of the times of neuro-pathic causes. To emphasize the validity of this investigation, data including personal, psycho-social and sexual history were gathered from the patients. The results demonstrated that only 3% of the 'Violeta Parra' clients/patients presented a significant repercussion of the Diabetes Mellitus in their sexuality. Nevertheless, one of the questions of this scale reflected that 75% of patients recognized that Diabetes Mellitus was the cause of their SED. It should be underlined here that 68% of the sample conveys to have a sexual erectile disorder, therefore the study demonstrated that Diabetes Mellitus has certain repercussion in the sexuality of males appointed to the Doctor's Office in Chillan.